Environmental factors shape the intestinal microbiota and function of Manila clam Ruditapes philippinarum - Bifu Gan; Guiling Li; Yanru Xu; Jingmiao Yang; Weilang Lin; Xiaobo Yan; Maozi Lin; Guangmao Ding; Fang Su; Qizhen Xiao (Frontiers in Marine Science, 2026)
Intestinal microbiota of aquatic animals is closely associated with the environment, influencing their health, immune defense, and environmental adaptability. To understand the relationships among the Manila clam ( Ruditapes philippinarum ) intestinal microbiota, the bacterial communities in their habitats, and environmental factors, as well as the characteristics and potential functions of the intestinal microbiota. This study systematically analyzed the bacterial communities in the clam intestines, seawater, and sediment samples from two typical habitats using 16S rRNA gene (V3-V4) sequencing. The results revealed significant differences in bacterial community composition among the intestines, seawater and sediment, with pronounced regional variations also evident within the same sample type. The clams gut microbiota in Fuqing was predominantly composed of Alphaproteobacteria , Gammaproteobacteria , Bacteroidota , Bacillota , and Cyanobacteria . In Putian, Cyanobacteria comprised an exceptionally high proportion. However, Bacillota , Bacteroidota , and Actinomycetota showed similar relative abundances in both regions, indicating a potential “core bacterial community”. Regarding the α-diversity of gut microbiota, although no significant differences were observed between clam samples from the two regions, their diversity was significantly lower than that of the sediment bacterial communities. The intestinal bacterial communities exhibited high similarity to the aquatic bacterial communities in terms of richness, diversity, and dominant species abundance, and it shares most of the ASVs with the sediment, suggesting that environmental microorganisms may serve as the primary source of the clam intestinal microbiota. Environmental drivers of bacterial communities differed regionally. In Fuqing, bacterial communities were associated with temperature, DO, pH, and salinity, and exhibited broader niche widths; in Putian, they were mainly influenced by nutrients, showing narrower niches. Compared to bacterial networks in the environment, the interactions among members within the gut bacterial communities of clams display modularity, indicative of functional specialization. The composition and functions of the intestinal microbiota of clams vary significantly in different environments, which may be a manifestation of their ecological adaptability. The composition and function of clam intestinal microbiota varied with environment, reflecting their ecological adaptability. These findings provide a scientific theoretical basis for water quality regulation and disease prevention in aquatic animal farming operations.

Tide-triggered N2O emission dynamics in saltmarsh wetlands of the Yangtze Estuary: Significance of N2O consumption - Manping Zhang; Chenchen Lixiang; Jianli Wen; Shanshan Sun; Xushun Gu; Shaoxuan Ding; Shengbing He; Guiling Liu (International Biodeterioration & Biodegradation, 2026)

Optimization of coal-based solid fuels for direct carbon fuel cells by chemical treatments - Yue Ding; Xuan Zhang; Shuyue Liu; Jinling Yin; Xianchao Wang; Jing Zhao; Qing Wen; Jiaxin Yao; Guiling Wang (Fuel, 2026)

Shaking table test on the seismic response of a multifloored grain warehouse structure considering the soil–structure interaction effect - Zhang Yanan; Xu Qikeng; Huang Yilin; Ding Yonggang; Wang Guiling (Soil Dynamics and Earthquake Engineering, 2025)

Dual-modal aptamer/CRISPR-Cas12a biosensor with Fe-C-N@Au nanozyme for simultaneous detection of azithromycin and macrolide resistance genes and degradation of azithromycin - Guiling Liu; Zongwu Meng; Wanshu Zheng; Anqi Qiu; Yuan Tian; Zerun Zhang; Tao Zhang; Pian Wu; Ping Ding (Journal of Hazardous Materials, 2025)

First record of the sap beetle Phenolia picta invading Eastern honey bee (Apis cerana) (Hymenoptera, Apidae) colonies - Lin Du; Wenbin Liu; Xiaoshun Chen; Jinge Licao; Guiling Ding; Zhanbao Guo; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2024)

High variation of worker cell and morphology between two adjacent populations of honey bee, Apis cerana (Hymenoptera, Apidae) - Rui Zhu; Weilai Zhong; Yuhui Chen; Guiling Ding; Zhanbao Guo; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2024)

High-directional thermally conductive stearic acid/expanded graphite - Graphene films for efficient photothermal energy storage - Zhaofeng Dai; Guiling Zhang; Yufei Xiao; Yulong Ding; Yongliang Li; Xiaohui She; Xiaosong Zhang; Dongliang Zhao (Chemical Engineering Journal, 2024)

Larger bees facilitate the deposition of oilseed rape pollen (Brassica napus L.) - Hongcai Chang; Zhijun Wei; Ran Liu; Guiling Ding; Jun Li; Jiaxing Huang (Journal of Asia-Pacific Entomology, 2023)

Immunodominant membrane protein (Imp) promotes the transmission of wheat blue dwarf (WBD) phytoplasma by directly interacting with α-tubulin in leafhoppers - Lei Ding; Wenjing Lu; Yanjun Yang; Qinrong Zhong; Tong Zhou; Guiling Wang; Chengyan Song; Wendong Ma; Wei Chen; Yunfeng Wu (European Journal of Plant Pathology, 2022)

Workers' sons rescue genetic diversity at the sex locus in an invasive honey bee population - Rosalyn S. Gloag; Joshua R. Christie; Guiling Ding; Ruby E. Stephens; Gabriele Buchmann; Benjamin P. Oldroyd (Molecular Ecology, 2019)
The hallmark of eusociality is the division of labour between reproductive (queen) and nonreproductive (worker) females. Yet in many eusocial insects, workers retain the ability to produce haploid male offspring from unfertilized eggs. The reproductive potential of workers has well‐documented consequences for the structure and function of insect colonies, but its implications at the population level are less often considered. We show that worker reproduction in honey bees can have an important role in maintaining genetic diversity at the sex locus in invasive populations. The honey bee sex locus is homozygous‐lethal, and, all else being equal, a higher allele number in the population lead to higher mean brood survival. In an invasive population of the honey bee Apis cerana in Australia, workers contribute significantly to male production: 38% of male‐producing colonies are queenless, and these contribute one‐third of all males at mating congregations. Using a model, we show that such male production by queenless workers will increase the number of sex alleles retained in nascent invasive populations following founder events, relative to a scenario in which only queens reproduce. We conclude that by rescuing sex locus diversity that would otherwise be lost, workers' sons help honey bee populations to minimize the negative effects of inbreeding after founder events and so contribute to their success as invaders.

Multi-functional Liposomes Enhancing Target and Antibacterial Immunity for Antimicrobial and Anti-Biofilm Against Methicillin-Resistant Staphylococcus aureus - Yansha Meng; Xucheng Hou; Jiongxi Lei; Mengmeng Chen; Shuangchen Cong; Yuanyuan Zhang; Weiming Ding; Guiling Li; Xinru Li (Pharmaceutical Research, 2016)